Pengaruh Kepemimpinan Komunikasi Lingkungan Kerja Dan Kompensasi Terhadap Semangat Kerja Karyawan Kjks Bmt Tumang Boyolali - Lestari, Dewi, Dr Fatchan Achyani, SE.Msi (2016)
Spirit of work is the willingness and eagerness in doing their job well to achieve the aim. The purpose of this research is to know the influence of leadership, communication, work environment and compensation toward employee's spirit. This reseach is done in KoperasiJasa Keuangan Syariah (KJKS) BMT TUMANG. The Sampling is the employees of BMT TUMANG with the number of people 66 employees by purposive sampling technique. The collecting of data use internal data of the company and questionair. The technique used in this reseach is Multiple Linier Regression. The result of this research shows that leadership, communication, work environment, and compensation influence the employees's work spirit.